Bilateral Tuberculous Otitis Media with Cerebellar Abscess in an Immunocompromised Child - Preetham S Dange; Prabhuraj Andiperumal Raj (Pediatric Infectious Disease)
Aim: Reporting a rare case of bilateral tuberculous otitis media with cerebellar abscess, its treatment and its outcome. Background: Mycobacterial tuberculosis is a rare cause of otitis media. Nevertheless, it is more commonly encountered in immunocompromised children. Delay in diagnosis and inadequate treatment can cause intra-cranial spread. Cases of tuberculous cerebellar abscess due to otitis media in immunocompromised patients have hardly been documented in literature. Case description: 7-year-old male child with HIV infection presented with History of ear discharge from 3 years and recent onset of cerebellar symptoms. He was diagnosed to have cerebellar abscess and was treated with twist drill aspiration and ventriculoperitoneal shunt. The child had recurrence of the abscess. Craniotomy and excision of the abscess was done. ZN staining of the pus showed Acid-fast bacilli. The child recovered with full course of anti-tubercular drugs. Conclusion: A tuberculous cerebellar abscess has a good prognosis even in an immunocompromised child if treated adequately. Clinical significance: Tuberculous etiology for otitis media must be suspected early in the presentation of an immunocompromised child with ear discharge especially when bilateral aggressive surgical approaches like craniotomy and excision must be considered when the disease is more wide spread such as in bilateral ear disease.